Impact of Islamic CSR and Intellectual Capital on the Maqashid Syariah Index in Indonesian Sharia Banks (2018-2022) - Putra, Yusuf Irvan Mahesa; Ekawati, Evi; Sisdianto, Ersi; Nurlaili, Nurlaili (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study examines the impact of Islamic Corporate Social Responsibility (ICSR) and Islamic Intellectual Capital (IIC) on the Maqashid Syariah Index, using theories such as stakeholder theory, Sharia Enterprise Theory, and Resource-Based Theory. The ICSR dimensions include Funding and Investment, Product and Service, Employee, Community, Environmental, and Governance, while the IIC dimensions cover Human Capital, Structural Capital, and Customer Capital. The research aims to analyze how these dimensions influence the Maqashid Syariah Index, which measures the achievement of Islamic principles in financial institutions. The study uses a quantitative approach, analyzing secondary data from the annual reports of eight Sharia Commercial Banks in Indonesia from 2018 to 2022. The sampling was done through purposive sampling, and data analysis was conducted using multiple linear regression with SPSS Statistics 25. The results reveal that the ICSR dimensions of Products and Services, Governance, and the IIC dimension of Structural Capital have a positive and significant impact on the Maqashid Syariah Index. However, the ICSR dimensions of Funding and Investment, Employee, Community, and Environmental, as well as the IIC dimensions of Human Capital and Customer Capital, show no significant effect on the Maqashid Syariah Index. This result indicates that certain aspects of ICSR and IIC are more critical in advancing the objectives of Islamic finance according to the Maqashid Syariah framework.